Fetal Aorta-Portal Vein-Umbilical Vein Anastomosis: Prenatal Diagnosis and Brief Review of Literature - Bhatt, Hitanshu R.; Nagraj, Gouri C. (Journal of Fetal Medicine, 2023)
Congenital hepatic arteriovenous fistulae (AVFs) are rare and occur in less than 1:100,000 live births and are linked with poor perinatal outcome. Hepatic arteriovenous malformation can be of three types, out of which we present a case of hepatic AVF with AV connection in a case of primigravida at 26 weeks gestation presented with fetal growth restriction and Doppler changes.
Keywords: congenital hepatic arteriovenous fistulae; fetal aorta-portal vein- umbilical vein anastomosis; fetal growth restriction; hepatic arteriovenous malformation; pseudo ductus venosus waveforms